Poéticas de multidão: autonomias co-(labor)ativas em rede - Nogueira, Isabelle Cordeiro (2008)
Different ways of communication relate to different ways of social organization. The historical and evolutionary process of the cultural production developed a context where digital media promote important transformations and where relationships in new space-time structures bring changes to the environment. In this conjuncture of change emerge the artistic production that is named here as Poetics of Multitude. In this poetics, the media assume a central role in the net collaborative autonomies that characterize them. For understanding them, it is necessary to identify new forms of living together with the writings of Bauman (2000, 2003), Santos (2005) e Souza Santos (2005, 2006), and with them, to reflect about globalization. In the perspective presented in this thesis, the body is treated as a primary media in accordance to the Bodymedia Theory, developed by Katz (2005) and Greinner (2005). Understood as a response to capitalism, the poetics of multitude is understood as a symptom of the contemporary society. The theory of Negri and Hardt (2004), and Virno (2002) sustains the research. In multitude - this new form of existence that contrasts to the ideas of folk or mass the poetics is related to autonomies in forms of net collaboration. And is present also in the creation and distribution of new ways of thinking dance. An interaction of neighbors , without the traditional practices of leadership and hierarchy promotes a kind of authonomy theoretically supported by concepts of evolution, co-adaptation and co-dependence (Dawkins (1976, 1978, 1998, 1999) and Dennett (1995). Such social systems auto-organize themselves through indirect control resembling what happens in other live systems (Gordon (2002) and Johnson (2003). Actions of the body in the world produce poetic emergences. We propose that the new forms of social organization that are being put in the world produce new ways of addressing knowledge and a new position to the subject